Effects of different root zone heating systems on microclimate and crop development in solar greenhouses - He, Fen; Tian, Jing; Wang, Liu; Hou, Yong; Qi, Fei; Zhang, Yanping; Zhu, Libao; Li, Zhonghua (International Journal of Agricultural and Biological Engineering, 2022)
Heating greenhouse is indispensable for plant development particularly in winter when the air temperature is lower. In that sense, root zone heating is more energy-saving than traditional air heating. The current work was devoted to the study of the effect of two root zone heating systems based on carbon crystal electrothermal film and low temperature hot water pipe on the microclimate and tomato yield in solar greenhouse. And their performance was tested in the coldest period of winter in Yongqing County of Hebei Province. The results showed that the use of root zone heating system can improve the average substrate temperature by 6.8°C. This microclimate improvement had a positive impact on the tomato production. The output per square meter has increased by 19% compared to the unheated. It was also noted that the presence of root zone heating leads to a decrease in the development of disease in heated areas. Based on these results, the root zone heating system can be an effective method of improving the environmental temperature of crop plant, which is of great significance for increasing crop yield. Keywords: solar greenhouse, root zone heating, substrate temperature, air temperature, tomato trough cultivation DOI: 10.25165/j.ijabe.20221506.7581 Citation: He F, Tian J, Wang L, Hou Y, Qi F, Zhang Y P, et al. Effects of different root zone heating systems on microclimate and crop development in solar greenhouse. Int J Agric & Biol Eng, 2022; 15(6): 67–72.